Synthesis and characterization of bipyridine and dipyridophenazine based ruthenium (ii) complexes as potential dye-sensitized solar cells sensitizers - Chan, Keng Fuong (2018)
Dye sensitizers are one of the key factors that affects the performance of dye-sensitized solar cells (DSSCs). One of the limitation of ruthenium bipyridyl sensitizer is the limited light absorption in infrared region. Hence, extended cyclic π-conjugated bipyridyl derivative was studied to overcome this limitation. Potential DSSC sensitizers such as 2,2’-bipyridine (bpy), dipyrido[3,2-a:2′,3′-c]-phenazine (dppz) and 11,12-dimethyldipyrido[3,2-a:2′,3′-c]-phenazine (dppx)-based ruthenium complexes were synthesized and characterized in this study. Three heteroleptic ruthenium complexes, namely cis-[Ru(dcbpy)(bpy)(NCS)2] (Rubpy), cis- [Ru(dcbpy)(dppz)(NCS)2] (Rudppz), and cis-[Ru(dcbpy)(dppx)(NCS)2] (Rudppx), where dcbpy = 2,2’-bipyridyl-4,4’-dicarboxylic acid, NCS- = isothiocyanate, were synthesized using a one-pot synthesis method and evaluated for their potential as dyesensitized solar cells (DSSCs) sensitizers. Spectroscopic, electrochemical and electron impedance spectroscopic analysis were performed on the as-synthesized ruthenium complexes. The commercial dye sensitizer, cis-[Ru(dcbpy)2(NCS)2] (N719) was used as a benchmark. The introduction of the dimethyl groups in the Rudppx complex resulted in a bathochromic shift (10 nm) in the intraligand absorption maximum at 384 nm, an enhancement in the molar absorption coefficient of the metal-to-ligand charge transfer band (λ = 500 nm), and the destabilization of both the ground and excited state molecular orbitals of the complex, compared to Rudppz. In terms of photovoltaic performance, Rubpy exhibited higher short circuit current density (2.07 mAcm-2) and power conversion efficiency (ɳ = 0.57%) as compared to Rudppz which had a short circuit current density of 1.52 mAcm-2 and a power conversion efficiency of 0.40%, demonstrating that the lower cyclic π-conjugation of the bipyridine ligand contributed to the lowest unoccupied molecular orbital in Rubpy that favoured electron injection. Rudppx exhibited improved power conversion efficiency (ɳ = 0.61%) as compared to Rudppz upon the introduction of the dipyrido [3,2-a: 2′,3′-c] -phenazine ligand which had dimethyl groups. The dimethyl groups behaved as electron-donating substituents that increased the electron density of the 11,12-dimethyldipyrido [3,2-a: 2′,3′-c] - phenazine ligand which helped in alternating the lowest occupied molecular orbital of Rudppx to enhance electron injection, resulting in an improved short circuit current density of 1.93 mAcm-2 from 1.52 mAcm-2 (Rudppz). The criteria for an efficient DSSC ruthenium-based sensitizer were drawn based on structure-property relationship studies of the ruthenium sensitizers in this study.